Evaluation the Quality of Measuring the Coordinates of Air Objects in the Synchronous Information Network of Surveillance Systems - Semenets, V.; Svyd, I.; Obod, I.; Maltsev, O.; Vorgul, O.; Tkach, M.; Chumak V. (My University, 2021)
The paper shows that the hereditary transition from asynchronous to synchronous networks of airspace surveillance radar systems in which time is one of the coordinates of the detected air objects, allows to calculate the height of air objects due to long-range measurements with the desired quality.
Keywords: Synchronous information network; information network; surveillance system; radar system; airspace surveillance; accuracy; air object; friend or foe; height measurement; reception center